Jurysdykcja i prawo właściwe dla stosunków między rodzicami a dzieckiem w relacjach polsko-ukraińskich - Pilich, Mateusz (Problemy Prawa Prywatnego Międzynarodowego, 2022)
The article pertains to the matter of jurisdiction and the law applicable to relations between parents and children in Polish-Ukrainian relations. In recent years, in particular since the beginning of Russia’s military aggression against Ukraine, large waves of Ukrainian immigrants have come to Poland. The structure of the migration, with the domination of women and children, oblige Polish courts and other authorities to deal with the issues of parental responsibility, contacts with children, custody and maintenance in the cross-border context. In this situation, the bilateral Agreement between the Republic of Poland and Ukraine on legal assistance and legal relations in civil and criminal matters, signed in Kiev on 24 May 1993, acquires a new significance. It contains both the procedural rules (on jurisdiction, international legal aid, service of documents, as well as the recognition and enforcement of judgments) and confl ict of law provisions in the field of broadly understood civil matters, including relations between parents and children. The author undertakes a critical analysis of the provisions of Polish-Ukrainian Agreement as with respect to filiation (children’s origin), parental responsibility and child maintenance. The anachronism of its solutions and the need for its termination is emphasized.